The motor learning approach and strategies in the treatment of children’s articulation disorders - Kairienė, Daiva (Special Education, 2017)
The article presents a theoretical analysis of the concept based on a motor learning approach as well as the possibilities for the application of this approach in speech and language therapy in the treatment of children’s articulation disorders. Motor learning principles have been emphasised as essential elements in speech and language therapy. They explain the importance of speech and language therapy services which are flexible and focused on individual cases. An analysis of theoretical sources focuses on the strategies of speech and language therapy based on the motor learning approach. These therapies differ between non-speech or speech levels. The aims of the application of these strategies and their theoretical presumptions of efficacy reveals the need for changes in the practice of speech and language therapists. An analysis of theoretical sources reveals that speech-based strategies of therapy are more efficient in learning correct sound pronunciation and promoting the intelligible speech of children. The application of non-speech oral motor therapy is purposeful in teaching non-speech movements of the articulatory system. When coping with children’s articulation disorders, it is necessary to differentiate strategies of motor learning with regard to the origin and level of a particular disorder.